Mortality Risks Among Persons Reporting Same-Sex Sexual Partners: Evidence From the 2008 General Social Survey—National Death Index Data Set - Cochran, Susan D.; Mays, Vickie M. (American journal of public health (1971), 2015)
Objectives. We investigated the possibility that men who have sex with men (MSM) and women who have sex with women (WSW) may be at higher risk for early mortality associated with suicide and other sexual orientation–associated health risks. Methods. We used data from the 1988–2002 General Social Surveys, with respondents followed up for mortality status as of December 31, 2008. The surveys included 17 886 persons aged 18 years or older, who reported at least 1 lifetime sexual partner. Of these, 853 reported any same-sex partners; 17 033 reported only different-sex partners. Using gender-stratified analyses, we compared these 2 groups for all-cause mortality and HIV-, suicide-, and breast cancer–related mortality. Results. The WSW evidenced greater risk for suicide mortality than presumptively heterosexual women, but there was no evidence of similar sexual orientation–associated risk among men. All-cause mortality did not appear to differ by sexual orientation among either women or men. HIV-related deaths were not elevated among MSM or breast cancer deaths among WSW. Conclusions. The elevated suicide mortality risk observed among WSW partially confirms public health concerns that sexual minorities experience greater burden from suicide-related mortality.